The distal β‐globin CACCC box is required for maximal stimulation of the β‐globin gene by EKLF - Marini, Maria Giuseppina; Asunis, Isadora; Porcu, Loredana; Salgo, Maria Giulia; Loi, Maria Giuseppina; Brucchietti, Arianna; Cao, Antonio; Moi, Paolo (British journal of haematology, 2004)
Summary The transcription factor erythroid Kruppel‐like factor (EKLF) specifically activates the β‐globin gene by interacting with the proximal β‐globin CACCC box, a known hot spot for thalassaemia mutations. This study investigated whether EKLF could also bind to, and activate from, the distal CACCC, which is a rare site of thalassaemia mutations. Using band shift and transient expression analysis with wild type, single and double CACCC mutants, we established that the distal CACCC box is weakly bound by EKLF, but, when mutated, significantly impairs EKLF‐dependent β‐globin stimulation. Thus, EKLF requires both CACCC boxes to maximally stimulate the β‐globin gene.